The Communicative Language Strategies of CEFR in TikTok Video - Santosa, Imam; -, Hana Syakirah (STAIRS: English Language Education Journal, 2024)
As a widely established scale a standardized assessment of language competency in Europe as well as worldwide, CEFR provides a clear baseline for assessing language ability. However, its representation in videos on TikTok, as one of the most potential language learning platforms remained unexplored. This study seeks to examine communicative language strategies linked with the CEFR in TikTok videos. Using a qualitative method and ATLAS.ti software, the data were collected from 200 videos using the hashtags #learnenglish and #communicationstrategies. Production was recognized as the most common communication strategy, with planning appearing in 43 videos. Moreover, videos in the B1 level were the most frequent, appearing in 86 videos. The results suggest that a systematic strategy, as seen in TikTok videos, requires a well-designed learning plan that includes regular intervals for listening, speaking, reading, and writing practice. Future studies should encourage educators to adopt these practices, to promote successful language education.